Characterization of particle and bulk solids of Arabic gum powder at different particle sizes - Rosland Abel, Stashia Eleaness (2022)
The use of Arabic gum as a functional food ingredient is growing rapidly. Arabic gum is obtained in the form of gum nodules from the exudation of stems and branches of Acacia Senegal (L.). Particle size is an important factor influencing powder properties and the end product’s quality. However, the food industry lacks information about the effects of particle size on the handling and processing of Arabic gum powder. Hence, this study investigated the particle size effects on Arabic gum powder's physicochemical, flow, rheological, and stability properties. The gum nodules were washed, dried, and cleaned before being ground, sieved, and fractionated into five particle size classes. The fractionation was classified according to its mean diameter (d50), which ranged from 20 to 1000 μm. The proximate composition analysis confirmed that particle size significantly affected the moisture and fibre contents of gum powder. Smaller particles have a higher hygroscopicity, with values of 40%, indicating that they are more prone to absorbing moisture from their surroundings. The dissolution analysis discovered that smaller particles dissolve in water more slowly than larger particles. The swelling index and emulsion capacity results show that larger particles retained more waterswollen granules and had a more remarkable ability to form an emulsion with oil. Meanwhile, morphology analysis discovered that the gum powder had an irregular shape with rough granule surfaces. On the other hand, a reduction in particle size from 1000 to 20 μm tends to reduce powder flowability. The highest Hausner ratio and Carr's index values were found in smaller particles, indicating poor powder flowability. Larger particles caked more, which is due to powder segregation during the handling process, with the coarser fraction dominating the overall caking behaviour of the powders. Furthermore, the larger particles had the highest effective angle of internal friction values due to their interlocking effect. Smaller particles had the highest effective angle of wall friction values, indicating that they will have more difficulty moving along the wall surface. Rheological analysis discovered that all particle sizes exhibited shear-thinning behaviour at low shear rates (0.1–50 s-1) and a viscosity plateau at high shear rates (50–400 s-1). Higher R2 validates the best-fitting power-law model for describing the aqueous solution's flow behaviour (n) and consistency index (K). Furthermore, the dynamic mechanical spectra curves revealed that the storage (G') and loss (G") moduli values increased with frequency, indicating that the highly concentrated gum exhibited solid-like rather than liquid-like behaviour. The isotherm curves had sigmoidal shapes and Type III behaviour, which is typical of sugar-rich products. The Peleg model fits the equilibrium moisture sorption of gum powder well. With SSE = 0.01, RMSE = 0.014, P = 14.14%, and R2 = 0.999, smaller particles provided the best fitting accuracy. To summarize, Arabic gum with coarse particles sized 208 to 414 μm demonstrated greater dissolution time, flowability, elasticity, and stability than other particle sizes. The ability to predict moisture content during storage under a variety of conditions can reduce product development costs and cycle time while also improving shelf life estimation. Furthermore, this comprehensive study of Arabic gum powder’s physicochemical properties will aid in the development of food products with the desired texture by allowing for the selection of a specific particle size.